Synthesis, characterization, computational and biological evaluation of pyrazole hydrazones as promising anti-inflammatory agents - Deshmukh, Hemant S.; Adole, Vishnu A.; Frit, A. Alfind Paul; Mali, Suraj N.; Yasin, Haya Khader Ahmad; Patil, Bhausaheb N.; Janani, S.; Jagdale, Bapu S. (Scientific Reports, 2025)
In this study, two pyrazole-based hydrazone derivatives, 5-methyl-1-phenyl-4-(1-(2-phenylhydrazineylidene)ethyl)-1H-pyrazole (PMPH) and 1-(4-fluorophenyl)-5-methyl-4-(1-(2-phenylhydrazineylidene)ethyl)-1H-pyr azole (4F-PMPH), were synthesized and the structures of the compounds were elucidated through FT-IR, 1H and 13C NMR, and mass spectral methods. The anti-inflammatory potential was evaluated using the bovine serum albumin denaturation assay, with PMPH and 4F-PMPH showing maximum inhibition at 0.5 mg/mL, respectively, suggesting that fluorine substitution enhances bioactivity. Molecular docking studies against COX-II (PDB: 3LN1) revealed favorable binding energies of - 7.21 kcal/mol (PMPH) and - 8.03 kcal/mol (4F-PMPH). Molecular dynamics simulation of the best docked compound 4F-PMPH with COX-II (PDB: 3LN1) revealed a stable complex over a 100 ns simulation, supporting its potential as a promising inhibitor. In silico ADME analyses revealed pharmacokinetic behavior and drug-likeness. A comparative Density functional theory-based spectroscopic and electronic investigation was conducted using the B3LYP/6-31G(d,p) level of theory. Vibrational frequency analysis showed strong correlation between theoretical and experimental IR spectra. Frontier molecular orbital analysis, molecular electrostatic surface potential maps, Mulliken charges, electronic and global reactivity parameters were also studied. Besides, reduced density gradient, non-covalent interaction, electron localization function, and localized orbital locator maps were analyzed for both the compounds.
Keywords: Anti-inflammatory; Density functional theory; Drug design; Hydrazone; Pyrazole